A rare case report of relapsed/refractory primary cutaneous diffuse large B-cell lymphoma, leg type, treated with Epcoritamab: results obtained and lesson learned - Cafaro, Alessandro; Malaspina, Francesco; Rossi, Pietro; Riemma, Costantino; Rosa, Jessica; Liardo, Eliana Valentina; Parolini, Margherita; Medri, Matelda; Silimbani, Paolo; Crudi, Laura; Masini, Carla; Musuraca, Gerardo (Frontiers in Oncology, 2026)
Primary Cutaneous Diffuse Large B-Cell Lymphoma, Leg Type (PCDLBCL-LT), is a rare and aggressive subtype of primary cutaneous B-cell lymphoma, predominantly affecting elderly individuals. The disease presents with nodular or tumorous skin lesions, mainly on the legs, and follows a highly aggressive clinical course, with frequent relapses and poor prognosis. The standard first-line treatment involves Rituximab-based chemoimmunotherapy (R-CHOP), but therapeutic options for relapsed or refractory cases remain limited. We report the case of a 72-year-old male with relapsed/refractory PCDLBCL-LT who achieved a remarkable but short-lived response to Epcoritamab, a novel bispecific antibody targeting CD3 and CD20. After multiple treatment lines, including R-COMP, Tafasitamab-Lenalidomide, and Polatuzumab-Rituximab, the patient received Epcoritamab as fourth-line therapy. Despite an initial clinical response with regression of cutaneous lesions, early relapse occurred, coinciding with loss of CD20 expression, likely due to prolonged Rituximab exposure. This highlights an already described mechanism of resistance in T cell-CD20-directed therapies. To our best knowledge, this is the first reported case of relapsed/refractory PCDLBCL-LT treated with a bispecific antibody targeting CD20 alone, without a previous CAR T.